ATM time series, 1967-2017 - Bernardo Bátiz-Lazo (The European Association for Banking and Financial History (EABH), 2018)
This short note is a description of the dataset compiled during the drafting of Cash and Dash: How ATMs and Computers Changed Banking (Oxford University Press, 2018). The full dataset is deposited with the European Association for Banking and Financial History, and is available for download from the association's website.
Keywords: G21; N20; N22; N24; 330; banking and technology; datasets